Multisystem involvement in hydatid disease: a case report of disseminated echinococcosis - Mallannagouda, Hanamanthraya; Melkundi, Shivanand; Devarmani, Sanjana; Tiwari, Vedashree V. (Frontiers in Parasitology, 2025)
BackgroundHydatid disease is a zoonosis caused by the larval stage of Echinococcus granulosus, most often affecting the liver and lungs. Disseminated hydatidosis is rare, accounting for <10% of cases.Case presentationWe present a 28-year-old man with paraplegia and abdominal pain. He was first diagnosed with hydatid disease at a government hospital 3 years earlier and presented to us with only an ultrasound (US) report. No serology reports were furnished. He had deferred surgery due to financial constraints. At current presentation, US, computed tomography (CT), and magnetic resonance imaging (MRI) demonstrated multiple cysts across the pelvis, retroperitoneum, spine, mediastinum, neck, and extremities. Imaging morphology was consistent with the WHO-IWGE (Informal Working Group on Echinococcosis) CE1–CE3 hydatid cysts. Differentials including abscess, cysticercosis, necrotic metastases, and lymphangioma were ruled out based on the absence of contrast enhancement, calcification pattern, and clinical correlation.Treatment and outcomeSurgery was advised, but was declined. PAIR (puncture, aspiration, injection, re-aspiration) was contraindicated due to multivesicular bone and spinal cysts. The patient was managed with oral albendazole. Follow-up data are currently unavailable.ConclusionThis case highlights disseminated hydatid disease with an unusual spinal and soft tissue involvement. Multimodality imaging is pivotal for diagnosis and treatment planning. Awareness of the imaging features is essential for timely recognition and management.